1992
DOI: 10.1111/j.1095-8649.1992.tb02711.x
|View full text |Cite
|
Sign up to set email alerts
|

Suction volume and filtering efficiency of silver carp (Hypophthalmichthys molitrix Val.) and bighead carp (Aristichthys nobilis Rich.)

Abstract: Experiments were conducted to measure the suction volume of silver carp and bighead carp of age I + with respiratory chamber, and to calculate the suction volume and the filtering efficiency with respect to changes in concentrations of food particles.Suction volume (B, ml/mouth) and filtering efficiency (E, %) were calculated using the following formula:where C,,and C,were theconcentrationsofspecific food particlesat the beginningandattheendof experiment, respectively, Vwas thevolume (ml) ofexperimental water,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Filtration efficiency of non-motile foods by bigheaded carps is largely controlled by the size of the particle (Dong et al, 1992). Microcystis is colonial and the colony sizes are large enough to be efficiently filtered by bigheaded carps.…”
Section: Discussionmentioning
confidence: 99%
“…Filtration efficiency of non-motile foods by bigheaded carps is largely controlled by the size of the particle (Dong et al, 1992). Microcystis is colonial and the colony sizes are large enough to be efficiently filtered by bigheaded carps.…”
Section: Discussionmentioning
confidence: 99%
“…Stable isotopes measure the chemical components assimilated by consumers over time and are hence better indicators of animal feeding and assimilation. Although zooplankton is only a small proportion of the instantaneous gut content, both silver carp and bighead carp have the capacity to filter large amounts of water and may obtain sufficient zooplankton to meet their daily dietary requirements (Dong et al 1992). Recent studies have also shown that both silver carp and bighead carp often have a dramatic impact on zooplankton abundance in lakes and experimental systems (Yang et al 1999;Xie and Yang 2000;Shao et al 2001;Wang et al 2007).…”
Section: Trophic Niche Overlap and Segregationmentioning
confidence: 99%
“…The estimated water velocity generated by the pipette strike was 30 cm s -1 , which is within the range of velocities generated by suctionfeeding planktivorous fish (Ferry-Graham et al, 2003). The volume of a single stroke of the pipette was about 2.5 ml, which is roughly equal to, e.g., suction volume of a 15-cm-long silver carp (Dong et al, 2006). To ensure random pipetting, at each transfer the source container was covered with an opaque wrapping, and the pipette tip was placed randomly at different spots in the container at subsequent strokes.…”
Section: Methodsmentioning
confidence: 73%